Analysis of the Physical Condition of Male Outdoor Hockey Athletes in East Java - Putra, Hanas Hutama Arinsa; Hariadi, Imam (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The purpose of this research is to identify and evaluate the physical condition profile of outdoor hockey athletes in East Java Province comprehensively. The research method employs a survey research design with a quantitative descriptive approach. Sampling is conducted using purposive sampling with a sample of 18 male outdoor hockey athletes registered in PUSLATDA East Java 2024. The instruments used in this research include physical condition tests comprising cardiorespiratory endurance (multi-fitness stage test), speed (20-meter sprint), agility (Illinois agility run), leg muscle explosiveness (standing triple jump), arm muscle strength (push up), abdominal muscle strength (sit up), back muscle strength (back up), and flexibility (sit and reach test). Based on the research results, it is shown that: (1) Cardiorespiratory endurance achieved a percentage of 87% categorized as good; (2) Leg muscle explosiveness achieved a percentage of 67% categorized as sufficient; (3) Speed achieved a percentage of 68% categorized as sufficient; (4) Agility achieved a percentage of 83% categorized as good; (5) Abdominal muscle strength achieved a percentage of 83% categorized as good; (6) Arm muscle strength achieved a percentage of 89% categorized as very good; (7) Back muscle strength achieved a percentage of 85% categorized as sufficient; (8) Flexibility achieved a percentage of 96% categorized as very good. Based on the overall results of the physical condition tests of the male outdoor hockey athletes from East Java, who have not yet demonstrated ideal performance to support the activities of male outdoor hockey athletes from East Java, a training program is required to improve the physical condition of the male outdoor hockey athletes from East Java as a whole.